Childhood Physical and Sexual Violences as Potential Factors of Post Traumatic Stress Disorder: A Meta-Analysis - Fadila Alfiasari; Didik Tamtomo; Hanung Prasetya (Masters Program in Public Health, 2023)
Background: WHO states that as many as 300 million children have experienced physical punishment or psychological violence. These traumatic events can cause Post Traumatic Stress Disorder (PTSD) which has an impact on the lives of victims of physical and sexual violence. The purpose of this study was to analyze and estimate the average influence of physical and sexual violence in childhood on the incidence of Post Traumatic Stress Disorder (PTSD) using a meta-analysis study.Subjects and Method: This research is a systematic review and meta-analysis with the selection of PRISMA flow diagrams. Population= adults aged >18 years. Intervention= experience of physical and sexual violence as children. Comparison= no experience of physical and sexual violence as children. Outcome= PTSD. Article searches through journal databases include: Pubmed, Google Schoolar, Science Direct, Researchgate and Springerlink. The articles used in this study are articles that have been published from 2000-2022. The keywords used in the database are “Child Physical Abuse”[tw] OR “Childhood Physical Abuse”[tw] OR “Child Maltreatment”[tw] OR “Physical Violence”[tw] OR